Assessing Walkability in Sulaimani City Center - Radha, Roza Abdullatif; Mohammed-Amin, Rozhen Kamal; Ali, Alan Faraydoon (Kurdistan Journal of Applied Research, 2020)
Walkability within urban design and planning context refers to urban environments that are friendly and supportive for the pedestrian. Walkable environments offer many economic, social, health, and environmental benefits and contribute to UN Sustainable Development Goals (SDGs). In public places, including city centers, walkability is a major asset for making them vibrant by attracting and maintaining pedestrians, including tourists. It is no coincidence that the top tourist destinations and livable cities as well as popular city centers and streets all share walkability character. Walkability quality in city center streets and any urban environment require planning. Good planning needs to be informed by measuring and assessing the state of walkability in existing streets and environments. While the literature presents systematic walkability assessment studies from different city centers of developed and developing countries, such studies are rare in the context of many other developing regions and countries like the Kurdistan Region and the rest of Iraq. Since walkability character can be contextual and affected by different socio-economic and environmental factors and dynamics, systematic and comprehensive assessment of under-researched environments and city centers are essential. To address this gap in the literature, this study systematically assesses the state of walkability in the city center of Sulaimani, the cultural capital of the Kurdistan Region of Iraq, and a UNESCO creative city in literature. This paper report results from assessing and comparing the physical characters of the six major interconnecting streets (Mawlawy, Kawa, Sabunkaran, Peramerd, Goran, and Bekas streets) in the center of Sulaimani city. The assessment considers the five main walkability factors of function, safety, destination, aesthetic, and comfort identified from the literature.